EMA/CO Combination Chemotheraphy in Gestational Trophoblastic Neoplasia: Update of Our Results - Tolga Taşçı; Işın Üreyen; Günsu Kimyon; Alper Karalök; Sevgi Koç; M. Faruk Köse; Gökhan Tulunay; Taner Turan (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we aimed updating our experience about the treatment success of EMA-CO (etoposide, methotrexate, actinomycin-D, cyclophosphamide, vincristine) chemotherapy in high-risk gestational trophoblastic neoplasia (GTN).